Glucose-dependent Secretion and Destruction of Hydrogen Peroxide by Mycoplasma pneumoniae - Cohen, Gerald (1969)
The secretion of H(2)O(2) by Mycoplasma pneumoniae and M. gallisepticum was measured with the new catalase-aminotriazole method. Peroxide secretion by the mycoplasmas was stimulated by glucose. When catalase and aminotriazole were omitted and exogenous H(2)O(2) was added to the mycoplasmas, a loss in H(2)O(2) was noted with time; the addition of glucose speeded the disappearance of H(2)O(2). The presence of this peroxidase-like activity in the mycoplasmas explains an observed failure of H(2)O(2) to accumulate freely in the suspension medium.